Targeting low-risk myelodysplastic syndrome with novel therapeutic strategies. Issue 10 (October 2021) - Trivedi, Gaurang; Inoue, Daichi; Zhang, Lingbo
Abstract : Myelodysplastic syndrome (MDS) is a group of hematopoietic disorders with limited treatment options. Anemia is a common symptom in MDS, and although erythropoiesis-stimulating agents such as erythropoietin, lenalidomide, and luspatercept are available to treat anemia, many MDS patients do not respond to these first-line therapies. Therefore, alternative drug development strategies are needed to improve therapeutic efficacy. Splicing modulators to correct splicing-related defects have shown promising results in clinical trials. Targeting differentiation of early erythroid progenitors to increase the erythroid output in MDS is another novel approach, which has shown encouraging results at the pre-clinical stage. Together, these therapeutic strategies provide new avenues to target MDS symptoms untreatable previously. Highlights: Myelodysplastic syndrome (MDS) is characterized by ineffective hematopoiesis arising from mutations in hematopoietic stem cells. Erythropoiesis-stimulating agents are the first choice of drugs for low-risk MDS patients but are often ineffective. Splicing factor mutations are the major class of mutation in MDS and recently developed splicing modulators can specifically target these mutations. Enhancing differentiation of early erythroid progenitors via inhibition of cholinergic receptor muscarinic 4 (CHRM4), a newly identified negative regulator of burst-forming unit erythroid (BFU-E) differentiation, has shown promising results in pre-clinical testing. Detailed investigation of nervous system regulation of hematopoietic stem and progenitor cell (HSPC) differentiation could unravel novel regulatory mechanisms of hematopoiesis.